2003
DOI: 10.1088/0741-3335/45/5/308
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent transport reduction byE Bvelocity shear during edge plasma biasing: recent experimental results

Abstract: Experiments in the tokamaks TEXTOR, CASTOR, T-10 and ISTTOK, as well as in the reversed field pinch RFX have provided new and complementary evidence on the physics of the universal mechanism of E × B velocity shear stabilization of turbulence, concomitant transport barrier formation and radial conductivity by using various edge biasing techniques.In TEXTOR the causality between transport reduction and induced electric fields in the edge has been for the first time clearly demonstrated. The high electric field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(35 citation statements)
references
References 52 publications
4
31
0
Order By: Relevance
“…Subsequently, many experiments have used external bias to study modification of the plasma turbulence and transport. [5][6][7][8] Recent experiments [8][9][10] in the upgraded Large Plasma Device 11 (LAPD) at the University of California, Los Angeles (UCLA) have studied the effect of the sheared flow on the edge turbulence and turbulent transport by biasing a section of the vacuum chamber wall. Linear and nonlinear simulations to model the plasma instabilities based on LAPD parameters are also developed.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, many experiments have used external bias to study modification of the plasma turbulence and transport. [5][6][7][8] Recent experiments [8][9][10] in the upgraded Large Plasma Device 11 (LAPD) at the University of California, Los Angeles (UCLA) have studied the effect of the sheared flow on the edge turbulence and turbulent transport by biasing a section of the vacuum chamber wall. Linear and nonlinear simulations to model the plasma instabilities based on LAPD parameters are also developed.…”
Section: Introductionmentioning
confidence: 99%
“…The predicted ion loss currents were in the range ≈15-150 Amps, which is comparable to the currents used to create H-modes in the electrode biasing experiments [6,7]. However, there are many limitations, uncertainties and omissions in the modeling, as described in the next section.…”
Section: Icrh Modelingmentioning
confidence: 64%
“…Edge electrode biasing experiments have certainly shown that an externally imposed radial current of ≈20-200 A can create an H-mode-like transport barrier [6,7], and a clear correlation has been shown between edge potential changes and the L-H transition [8]. Thus it would be useful if some non-intrusive means could be found to control ion loss to the wall and thereby control the H-mode transition.…”
Section: Introductionmentioning
confidence: 99%
“…2 have been registered at a radial position of r p = 79 mm, the Katsumata tunnel is oriented upstream to the toroidal plasma current. During a part of the flat top phase of the discharge, an additional electrode, inserted radially at r E = 60 mm near the position of the last-closed flux surface (LCFS) was biased to a voltage of +100 V. A more detailed description of the biasing experiment on CASTOR can be found in [8]. Fig.…”
Section: Segm1 Segm2mentioning
confidence: 99%